DEVELOPMENT AND VALIDATION OF AN RP-HPLC METHOD FOR DEFERIPRONE ESTIMATION IN PHARMACEUTICAL DOSAGE FORM - KOTHAWADE, SACHIN N; V PANDE, VISHAL (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: For the simultaneous estimation of deferiprone in pharmaceutical formulations, a high-performance liquid chromatographic technique that is straightforward, reproducible, and effective was developed. Methods: The Advanced Technologies Ltd HPLC system with a UV-2075 UV-Vis detector, P-2080 HPLC pump, and a Hypersil C18 column (250 × 4.6 mm) was used to perform the chromatographic separation. ACN and water make up the mobile phase (55:45 v/v). The solvent system was flowing at a rate of 1.0 mL/min. 4.7 g of sodium dihydrogen orthophosphate and 1 mL of triethyl amine were used as the buffer, and orthophosphoric acid was used to bring the pH of the solution to 4.0 ± 0.05. The sample volume was 20 μL, as well as the temperature range, was kept at room temperature. Results: The method was approved for the rapid screening and confirmed in conformance with ICH guidelines. For the purpose of determining the presence of deferiprone in active ingredients, an RP-HPLC analysis model with Uv spectrophotometer has been developed. The drug determination retention time (4.960 min), which is crucial for routine analysis. The method’s high sensitivity was indicated by the low identification and qualifying limits. Conclusion: The developed method for simultaneously determining Deferiprone in pharmaceutical formulations was found to be more accurate, precise, and selective.